Infertility from clinical and social perspective - Kurzawa, Rafał; Kaniewska, Dorota; Bączkowski, Tomasz (Przewodnik Lekarza/Guide for GPs, 2010)
Both male and female infertility has multifactoral origin. Even small disturbances, can have considerable influence on human reproduction.. Infertility is not only a medical conditions, stress and other psycho-social factors additionally can contribute to lower pregnancy rates. Treatment should be individualized. The medical personal should consider not only patients’ medical status but also economical conditions and ethical views. As conservative methods of treatment have limited efficacy, assisted reproductive techniques are widely used to treat infertility.